Análise da complexidade econômica na cadeia global de valor do agronegócio no Brasil para o ano de 2014 - Chaves, Thainá de Matos Grote (2021)
Globalization and global technological changes carry with itselves marked transformations in the industrial and commercial paradigm that are spread, mainly, through international productive fragmentation and the growth of Global Value Chains (GVC). The analysis of GVCs is highly relevant to assess the strategic positioning of countries and sectors and how they have been modernized or developed. Thus, the differences between rich and poor countries, and the discussion between “center and periphery” in CGVs point out to the presence of greater economic complexity (EC) in the so-called central, or richer, countries. The present work seeks to deepen the analysis of the Brazilian agribusiness insertion in GVCs by applying the methodology for decomposing gross exports proposed by Wang, Wei and Zhu (2014; 2018). This methodology disaggregates gross exports geographically and by sectors, broken down into several components that allow a better identification of domestic and foreign exports value added and, thus, deepen the characterization of countries integration in GVC. Using data from the WIOD database for 2014, the Brazilian insertion in GVCs is examined in a perspective compared to selected countries, and then the analysis is made for the agribusiness component sectors as an aggregate, as well as in a disaggregated way for each sector, to view which sectors are most relevant for the country. According to the analysis of exports, it is confirmed the low integration of Brazil in GVCs. The country's specialization in natural resources is one of the explaining factors, since the domestic value added is mostly exported under the form of agricultural and/or industrial commodities, so that this ends up being the main form of insertion in GVCs. This reveals a worry by the EC literature, since these chains where Brazil’s take part have low EC.